2014
DOI: 10.1038/ncomms6626
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous long-range antiferromagnetic coupling across the interface between superconducting and ferromagnetic oxides

Abstract: The so-called proximity effect is the manifestation, across an interface, of the systematic competition between magnetic order and superconductivity. This phenomenon has been well documented and understood for conventional superconductors coupled with metallic ferromagnets; however it is still less known for oxide materials, where much higher critical temperatures are offered by copper oxide-based superconductors. Here we show that, even in the absence of direct Cu-O-Mn covalent bonding, the interfacial CuO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…The XMCD signal at 100 K (Fig. 5(f)) is ambiguous for S2 and can be interpreted as unclear magnetism, similar to that reported earlier in a similar system 21 . It was reported that at 100 K, there was no Cu magnetic moment for a 25 u.c.…”
Section: Resultssupporting
confidence: 85%
“…The XMCD signal at 100 K (Fig. 5(f)) is ambiguous for S2 and can be interpreted as unclear magnetism, similar to that reported earlier in a similar system 21 . It was reported that at 100 K, there was no Cu magnetic moment for a 25 u.c.…”
Section: Resultssupporting
confidence: 85%
“…The second possibility, where the paramagnetic Cu XCMD originates from bulklike Cu ions, was suggested in Ref. [36], which reported similar XMCD data for corresponding LSCO/LCMO MLs. Nevertheless, as shown in the following, we can exclude such a two-component scenario for the case of these YBCO/LCMO MLs.…”
Section: B Two-component Scenario With Paramagnetic Bulklike Cu Ionsmentioning
confidence: 56%
“…An additional argument against the two-component scenario of Ref. [36] is that such a paramagnetic signal is not observed in YL 1, despite the circumstance that this sample contains the same amount of bulklike Cu ions as YL 2.…”
Section: B Two-component Scenario With Paramagnetic Bulklike Cu Ionsmentioning
confidence: 87%
“…Such systems allow the study of antagonistic superconducting and ferromagnetic order parameters, giving rise to exotic behaviors. A prominent example of a resulting effect can be found in the magnetic proximity effect which gives rise to a strong suppression of the FM moment of the Mn ions on the manganite side of the interface and yet a small induced FM moment of the Cu ions (that is antiparallel to the one of Mn) on the cuprate side [10][11][12][13][14][15][16][17]. The systems that are studied in most cases are superlattices (SLs) combining the cuprate YBa 2 Cu 3 O 7−x and the manganite La 1−x (Sr,Ca) x MnO 3 since the similarity of their lattice constants results in sharp and coherent epitaxial interfaces [12,18].…”
Section: Introductionmentioning
confidence: 99%